Fatty acid composition of six freshwater wild cyanobacterial species - Rezanka, T; Dor, I; Prell, A; Dembitsky, V M (Folia microbiologica, 2003)
Hydroxy, n-saturated, branched, dioic, and unsaturated fatty acids in six freshwater wild cyanobacteria (Chroococcus minutus, Lyngbya ceylanica, Merismopedia glauca, Nodularia sphaerocarpa, Nostoc linckia, and Synechococcus aeruginosus) collected from different lakes and springs of Israel have been identified by gas chromatography-mass spectrometry (GC-MS).
Keywords: sladká voda; sinice; Izrael; Bacterial Typing Techniques; mastné kyseliny; plynová chromatografie s hmotnostně spektrometrickou detekcí; Cyanobacteria; Gas Chromatography-Mass Spectrometry; Israel; Fresh Water; techniky typizace bakterií; Fatty Acids